2017
DOI: 10.3390/en10030274
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Shell-and-Tube Type Latent Thermal Energy Storage Performance with Different Arrangements of Circular Fins

Abstract: Latent thermal energy storage (LTS) systems are versatile due to their high-energy storage density within a small temperature range. In shell-and-tube type storage systems fins can be used in order to achieve enhanced charging and discharging power. Typically, circular fins are evenly distributed over the length of the heat exchanger pipe. However, it is yet to be proven that this allocation is the most suitable for every kind of system and application. Consequently, within this paper, a simulation model was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This work agrees with earlier work [17,32,[93][94][95][96][97][98][99][100][101] in concluding that fins are an effective strategy for the enhancement of heat transfer within LHTSDs. However, it qualifies that conclusion by noting that the flow and melt boundary develop in similar ways in both cases despite the significant differences in geometry.…”
Section: Analysis Of Melt and Flow Behavior During Dischargingsupporting
confidence: 92%
See 1 more Smart Citation
“…This work agrees with earlier work [17,32,[93][94][95][96][97][98][99][100][101] in concluding that fins are an effective strategy for the enhancement of heat transfer within LHTSDs. However, it qualifies that conclusion by noting that the flow and melt boundary develop in similar ways in both cases despite the significant differences in geometry.…”
Section: Analysis Of Melt and Flow Behavior During Dischargingsupporting
confidence: 92%
“…However, the most common (and cost-effective) strategy to enhance heat transfer into and out of a PCM thermal storage unit is the use of high conductivity fins [17,32,93]. Previous computational and experimental work on finned heat spreaders demonstrates that they consistently enhance heat transfer within a variety of types of LHTSDs [94], including containers with flat plate fins [95,96], axial fins [97,98], and circular fins [99][100][101].…”
Section: Introductionmentioning
confidence: 99%
“…SCHPs are used in the cooling of electronics, in space applications as well as in thermal energy storage systems [1]. Various studies have been carried out to investigate their performance in such applications [6][7][8][9][10][11][12]. On the other hand, RHPs are mainly used in applications such as the cooling of drill tips [13], cooling of rotating electrical machines [14][15][16] and heating/cooling of metal strips [17].…”
Section: Introductionmentioning
confidence: 99%
“…Most noticeable is the recent trend of the shell-and-tube LHS unit being integrated into solar thermal power systems, as seen in the applications studied by Li et al [4] and Tehrani et al [5]. Consequently, the shell-and-tube type LHS unit was the subject of a number of analytical [6][7][8][9], experimental [10][11][12][13], and numerical [14][15][16][17][18][19][20][21][22] studies, which focused mostly on performance enhancements at the charging/discharging-stage of the unit.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that proper arrangements of the hierarchical inner tube design can decrease melting time. Along the same line of geometric investigations, Darzi et al [16], Tabassum et al [19], and Kuboth et al [21] explored new ideas of geometrically altering the shell-and-tube type LHS unit to enhance the heat transfer performance.…”
Section: Introductionmentioning
confidence: 99%